PENGARUH POLA USAHA PETERNAKAN AYAM BROILER TERHADAP RISIKO HARGA DAN PEROLEHAN PENDAPATAN BERSIH (Studi Komparatif Pada Peternak Mitra Pt.Ciomas Adisatwa Dan Peternak Mandiri Di Kabupaten Malang, Jawa Timur) - Aulia, Laily Nur (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to 1) analyze whether there is any income difference between partnership model farmers and independent model farmers; 2) analyze the magnitude of the price risk borne by partnership farmers and independent farmers; 3) analyze price risk management strategies applied by partnership and independent farmers. This study was a descriptive quantitative research that uses data collection techniques such as observation and  documentation. The number of  32  partnership farmers of  PT.  Ciomas  Adisatwa and  24 independent farmers is used as samples which are located in Malang. The independent sample t-test is used to determine whether there is a difference in net income of partnership and independent farmers, while the variance, standard deviation, coefficient of variance, and lower limit of revenue are calculated and used in the price risk analysis. The results show that: 1) there is no difference in the net income of partnership farmers and independent farmers; 2) partnership farmers face lower price risk compared to independent farmers; 3) partnership farmers and independent farmers must have strategies in managing price risk which the partnership business model is one of the efforts to mitigate price risk.Keywords: partnership, independent, net revenue, price risk, independent sample t-test, variance, standard deviation, coefficient of variance.